2014
DOI: 10.1016/j.bbmt.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Interferon-Alpha Production by Plasmacytoid Dendritic Cells after Cord Blood Transplantation in Children: Implication for Post-transplantation Toll-Like Receptor Ligand–Based Immunotherapy

Abstract: Plasmacytoid dendritic cells (pDCs) initiate both innate and adaptive immune responses, making them attractive targets for post-transplantation immunotherapy, particularly after cord blood transplantation (CBT). Toll-like receptor (TLR) agonists are currently studied for pDC stimulation in various clinical settings. Their efficacy depends on pDC number and functionality, which are unknown after CBT. We performed a longitudinal study of pDC reconstitution in children who underwent bone marrow transplantation (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…No significant differences were observed in NK cell activation depending on the pDC source ( Supplemental Figure S1 ). Accordingly, we have previously showed that in vitro differentiated pDCs produce large amounts of IFN-α upon TLR stimulation and display the same phenotype as mature peripheral blood pDCs [ 26 ]. A direct TLR-9 stimulation of NK cells by CpG ODN was ruled out, as CpG ODN alone did not increase NK cell cytotoxic activity against pre-B ALL cell lines ( Supplemental Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant differences were observed in NK cell activation depending on the pDC source ( Supplemental Figure S1 ). Accordingly, we have previously showed that in vitro differentiated pDCs produce large amounts of IFN-α upon TLR stimulation and display the same phenotype as mature peripheral blood pDCs [ 26 ]. A direct TLR-9 stimulation of NK cells by CpG ODN was ruled out, as CpG ODN alone did not increase NK cell cytotoxic activity against pre-B ALL cell lines ( Supplemental Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
“…We and others recently described that human CD34 + precursors can be cultured and differentiated in pDCs in vitro [ 26 , 30 ]. This method allows the production of high numbers of functional pDCs that can be activated by TLR ligands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important bridge between innate immune defense and acquired immunity, it can trigger signal transduction, which further leads to the release of inflammatory mediators by identifying pathogen-associated molecular patterns and certain endogenous ligands (8). A previous study found that TLR may play certain roles in pathogenesis and bio-immunotherapy (9).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study where plasmacytoid dendritic cells (pDC) were investigated after bone marrow or cord blood transplantation, pDC from cord blood recipients displayed impaired activation in response to stimulation with the TLR9 agonist CpG, possibly explaining the increased infectious rates and lower rates of aGvHD and GVT effects after cord blood transplantation, emphasizing the importance of TLR9 in alloreactivity. 51…”
Section: Tlr and The Graft Versus Tumor Effectsmentioning
confidence: 99%